Peran Komunikasi Kelompok dalam Pengambilan Keputusan Produksi Kopi Gemplong oleh Komunitas Subileng - Febriany, Febriany; Kartika, Vita Dwi; Arihni, Melysa; Astuti, Ferli Dewi (IAINU Kebumen, 2025)
This study aims to analyze the role of group communication in the decision-making process within the Subileng Community, a local initiative based in Giritirto Village, Karanggayam District, Kebumen Regency, in establishing the production of Kopi Gemplong (Gemplong Coffee). The community, composed of local residents, regularly holds discussion forums to address local issues, which gradually evolved into a participatory decision-making platform. This research employs a qualitative approach, with data collected through unstructured interviews with three key informants: the community founder, a cultural activist, and a coffee enthusiast. The analysis is grounded in the Functional Perspective on Group Decision Making, which highlights four stages of decision-making: problem analysis, goal setting, identification of alternatives, and evaluation of characteristics. The findings indicate that group communication serves as an effective medium for exchanging ideas, fostering collective awareness, and building consensus without coercion. Through open and democratic discussions, the Subileng Community successfully initiated the production of Kopi Gemplong by utilizing local natural resources and promoting community-based economic empowerment. Decisions related to production, product naming, and packaging were made through inclusive and reflective communication practices. This research demonstrates that group communication can be a strategic instrument in empowering local communities and facilitating sustainable development based on traditional values. The results offer valuable insights for other community groups seeking to implement group communication as a foundation for participatory, constructive, and socially impactful decision-making